Mouse model of radiation-induced premature ovarian insufficiency reveals compromised oocyte quality: implications for fertility preservation. Issue 5 (November 2021) - Puy, Vincent; Barroca, Vilma; Messiaen, Sébastien; Ménard, Véronique; Torres, Claire; Devanand, Caroline; Moison, Delphine; Lewandowski, Daniel; Guerquin, Marie-Justine; Martini, Emmanuelle; Frydman, Nelly; Livera, Gabriel
Abstract: Research question: What is the impact of radiation exposure on oocyte quality and female fertility? Design: Prepubertal mice underwent whole-body irradiation with a single dose (0.02, 0.1, 0.5, 2, 8 Gy) of gamma- or X-rays. Oocytes were quantified in irradiated ( n  = 36) and sham-treated ( n  = 8) mice. After a single exposure to 2 Gy, formation of DNA double-strand breaks ( n  = 10), activation of checkpoint kinase (Chk2) ( n  = 10) and dynamics of follicular growth ( n  = 18) were analysed. Fertility assessment was performed in adult irradiated mice and controls from the number of pups per mouse ( n  = 28) and the fetal abortion rate ( n  = 24). Ploidy of mature oocytes ( n  = 20) was analysed after CREST immunostaining, and uterine sections were examined. Results: Radiation exposure induced a massive loss of primordial follicles with LD50 below 50 mGy for both gamma and X-rays. Growing follicles survived doses up to 8 Gy. This difference in radiosensitivity was not due to a different amount of radio-induced DNA damage, and Chk2 was activated in all oocytes. Exposure to a 2 Gy dose abolished the long-term fertility of females due to depletion of the ovarian reserve. Detailed analysis indicates that surviving oocytes were able to complete folliculogenesis and could be fertilized. This transient fertility allowed irradiated females to produce a single litter albeit with a high rate of fetal abortion (23%, P  = 0.0096), related to altered ploidy in the surviving oocytes (25.5%, P  = 0.0035). Conclusions: The effects of radiation on surviving oocyte quality question natural conception as a first-line approach in cancer survivors. Together, the data emphasize the need for fertility preservation before radiation exposure and call for reassessment of the use of cryopreserved oocytes.